PENGEMBANGAN INOVASI PRODUK OLAHAN BANDENG DAN STRATEGI PEMASARAN ONLINE DALAM MENINGKATKAN PENDAPATAN MASYARAKAT KELURAHAN SAWAH LUHUR KOTA SERANG - Puspita Maelani; Mahfudoh Mahfudoh; Agustiawan Agustiawan; Euis Suhartini (Jurnal Abdimas Bina Bangsa, 2022)
Sawah sublime is one of the villages that has the potential for unique food that is in demand by the community, but sales and packaging still use traditional methods. The purpose of this service is to provide training to business groups in using the marketplace and modifying the packaging and processed milkfish as the main ingredient. This service activity method uses 3 stages, namely preparation, implementation and evaluation. As a result of this activity, the business group has skills in managing milkfish products, attractive packaging and sales using the marketplace, so that the income of the community itself increases. The importance of this service is that village codns have tourism and culinary potential but have not experienced a significant increase in income, with this service providing skills for business groups to develop their businesses, so that they will increase income